Clinical and functional analysis of RAC GTPASE activating protein (RACGAP1) as predictive biomarker for recurrence of hepatocellular carcinoma - Wang, Suk Mei (2010)
Hepatocellular carcinoma (HCC) is the sixth most common malignancy and the third most common cause of cancer-related death worldwide. Although early HCC is potentially curable by partial hepatectomy, postresection prognosis remains poor because of the high recurrence rate, as the overall 5-year survival rate is lower than 5%. The heterogeneous nature of human HCC has also limited the usefulness of conventional clinicopathological features available at diagnosis for both treatment and prediction of disease outcome Hence, better understanding of the clinicopathological features and molecular aspects of HCC to assess and stratify patients with different risks of disease recurrence at diagnosis would be extremely beneficial for the clinical management of HCC. In this study, we first attempt to systematically analyze and combine some of the conventional clinicopathological features available at diagnosis to segregate HCC patients with different risk of developing recurrence. We also employ molecular expression profiling to identify novel differentially regulated genes closely associated with recurrent disease to improve the prediction of HCC recurrence at diagnosis especially for patients who have 50% risk of developing disease recurrence.